Beyond Pensions: A Radical Systems-Based Transformation of Present-Future Choice. (1st September 2016) - Gerstenhaber, Moshe; Maital, Shlomo; Buchnik, Tsipy
Abstract : Aging populations worldwide, fiscal deficits, growing sovereign debt, and slowing economies have combined to create and exacerbate what is widely known as the "pension crisis", characterized by poverty among the elderly substantially due to inadequate retirement income. We argue that the roots of the crisis go much deeper than "pensions", and involve a long-term secular shift from saving and capital formation to consumption, in the West. Cosmetic "solutions" to the pension crisis, such as delaying the retirement age, are ineffective. The "pension crisis" label itself impedes clear thinking about developing an effective and affordable solution. The core of the problem is the fact that present-future choice tilted to "present", in the West, for decades. Higher saving, over a longer time horizon, invested at higher average returns, is the ultimate goal, and only one that offers true long-term transformative change. We propose an original, radical, systemic solution, based on an evolutionary social transformation 1 of present-future choice toward increased saving; a proposal that addresses the roots of the pension crisis, not just the symptoms. 2 We contend that an effective pension allocation and accumulation system is a stable force for economic growth over time — but only when these significant capital investments are made directly in the real economy and take account of appropriate technological innovation. At the moment the bulk of global investment capital in the West is directed to short-term speculative activity in various financial markets, opportunistically taking advantage of historically low borrowing rates. We provide a macroeconomic simulation of our proposal, should it be adopted, comparing no-change and radical-change scenarios for the Israel economy, and urge scholars to carry out similar projections and analyses for individual OECD countries. We next show how an increase in national saving and capital formation can contribute to "rebalancing" the global economy, between low-saving Western nations and high-saving Asian ones. Finally, we outline our "four pillar" radical proposal, which leverages persistent long-run saving and investment, and illustrate its impact with some macroeconomic projections for Israel, comparing two scenarios, one with low national saving, the second with increased national saving. An achievable increase in the national saving rate, implemented through the tax system and accompanied by intelligent capital formation, can have enormous impact, it is shown, not only on elderly poverty but on society as a whole. In our plan, lower consumption demand through higher savings, is offset by higher capital formation, which has a larger employment and GDP multiplier.